Citation distribution profile in Brazilian journals of general medicine - Lustosa, Luiggi Araujo; Chalco, Mario Edmundo Pastrana; Borba, Cecília de Melo; Higa, André Eizo; Almeida, Renan Moritz Varnier Rodrigues (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Impact factors are currently the bibliometric index most used for evaluating scientific journals. However, the way in which they are used, for instance concerning the study or journal types analyzed, can markedly interfere with estimate reliability. This study aimed to analyze the citation distribution pattern in three Brazilian journals of general medicine. DESIGN AND SETTING: This was a descriptive study based on numbers of citations of scientific studies published by three Brazilian journals of general medicine. METHODS: The journals analyzed were São Paulo Medical Journal, Clinics and Revista da Associação Médica Brasileira. This survey used data available from the Institute for Scientific Information (ISI) platform, from which the total number of papers published in each journal in 2007-2008 and the number of citations of these papers in 2009 were obtained. From these data, the citation distribution was derived and journal impact factors (average number of citations) were estimated. These factors were then compared with those directly available from the ISI Journal of Citation Reports (JCR). RESULTS: Respectively, 134, 203 and 192 papers were published by these journals during the period analyzed. The observed citation distributions were highly skewed, such that many papers had few citations and a small percentage had many citations. It was not possible to identify any specific pattern for the most cited papers or to exactly reproduce the JCR impact factors. CONCLUSION: Use of measures like “impact factors”, which characterize citations through averages, does not adequately represent the citation distribution in the journals analyzed.